Millimeter-wave device and circuit technology - Edwards, Terry (IEEE, 2010)
The main aim of this course is to provide the learner with a detailed understanding of millimeter-wave circuit technology. Strongly supported by diagrams and equations, the following aspects are included: Some appropriate semiconductor materials: silicon, SiGe, GaAs, GaN, InP, etc; Some associated transistor and MMIC technologies; The increasing importance of CMOS chip technology (both direct" CMOS and SiGe BiCMOS); The twin challenges of generally (solid-state) decreasing RF output power availability and increasing noise figure as frequency increases; Important transmission structures including microstrip and grounded co-planar waveguide (GCPW); An overview of an alternative transmission structure - PolyStrata (TM); Spatial power combining' the vitally important subject of packaging. It will generally be assumed that everyone taking this course will start with a working knowledge of RF and microwave engineering.